Recent Trends in Technology Research for Election Surveillance During 2014-2024: A Systematic Review - Wance, Marno; Muhtar; Herizal; Mutijima, Pacifique (Universitas Muhammadiyah Malang, 2025)
This study examines trends in publications on election monitoring technology from 2014 to 2025, utilizing data from the Scopus database. The PRISMA research method is a structured research approach that analyzes data through a series of diagrams. Through the stages of identification, screening, eligibility, and verification, 181 publication documents were found to be usable in the study. The research findings show that the highest number of publications occurred in 2014 with 32 and in 2023 with 23, while a decrease in the number of publications over the 12 years occurred in 2015 with 7 documents and in 2016 with 8 publications. The aspects of publication contributions based on the most countries were, in order, the United States, Indonesia, India, and China, which were the largest contributors with the most publications. The research studies that were often conducted explored issues of the impact of technology, election fraud, and the transparency of election administration. The research findings contributed 80 documents in the field of computer science, 69 documents in social science, and 69 documents in engineering. Contributions in the field of Computer Science focus on research related to information technology and data security. Contributions in terms of document types include 67 articles, 62 conference papers, and 17 book chapters. The novelty of this research lies in reinforcing recent studies on the use of technology to enhance transparency and fairness in elections. Additionally, researchers suggest the need for studies on information technology systems that can support electronic voting processes.